WOUND HEALING (International Journal of Food and Nutritional Sciences, 2022)
Acute and chronic wounds are the two main categories of skin wounds. Traumatic or surgical wounds are considered acute wounds, and they typically heal over time in accordance with the standard wound-healing protocol. Therefore, one of the most intricate processes in the human body is skin restoration. When a wound occurs, the wounded blood arteries constrict and platelets activate to produce a fibrin clot. Incoming inflammatory cells can find scaffolding from the fibrin clot, which also stops blood flow. The clot instantly attracts neutrophils as their first line of defense against germs. Within 48 to 96 hours of an injury, monocytes are drawn in and at the wound site, they differentiate into tissue-activated macrophages. Complications of cutanecous wound healing are Deficient scar formation, Excessive formation of components of repair process and Contracture which results in deformities and commonly seen after burns and results in restricted movement.